Cultural Competences: An Important Resource in the Industry–NGO Dialog - Joutsenvirta, Maria (Journal of business ethics, 2010)
This article explores the concept of cultural competence and its relevance as an organizational resource in ethical disputes. Empirically, we aim to reveal the cultural competences that a global forest industry company, StoraEnso, and a global environmental nongovernmental organization (NGO), Greenpeace, utilized in forestry conflicts during 1985–2001. Our study is based on data which were collected from corporate and NGO communication outlets and which have gone through a detailed discourse-semiotic analysis. Our reinterpretation of the discourses identified three cultural competences: (1) the ability to understand changing consumer preferences and values, (2) the ability to utilize culturally determined positions of expertise, and (3) the ability to maintain trust and credibility in the community through open communicative practices. We argue that these competences are relevant in industry–NGO disputes for both parties. However, maintaining them all simultaneously is a difficult task, since various discourses which aim at upholding them can sometimes have contradictory effects.